RI 4145 Investigation of Dillsburg Magnatite Deposits, York Co., PA - G. L. Neumann (The National Institute for Occupational Safety and Health (NIOSH), 1947)
"INTRODUCTION Mining in this area is inactive. The entire region is now comprised of small farms. Because approximately 1,500,000 tons of magnetite ore had been shipped from this area between 1855 and 1915, it was deemed probable that geophysical surveying and core drilling might indicate other ore bodies or sizable extensions of the previously mined ore bodies.ACKNOWLEDGEMENTSIn its program of investigation of mineral deposits, the Bureau of Mines has, as its primary objective, the most effective utilization of our mineral resources, thus fortifying our national security and economy. It is the policy of the Bureau to publish the facts developed by each project as soon as practicable after its conclusion. The Mining Branch, Lowell B. Moon, chief, conducts preliminary examinations, performs the actual investigative work and prepares the final report. The Metallurgical Branch, Oliver C. Ralston, chief, analyzes samples and performs beneficiatien tests.The chemical analyses and beneficiation tests included in this report were performed at the Eastern Experiment Station of the Bureau of Mines at College Park, Md., under the general supervision of J. B. Zadra, chief, College Park Division, Metallurgical Branch, and the immediate direction of Dr. Alton Gabriel, head of the laboratory service unit.The Mineral exploration Was under the general supervision successively of G. D. Jermain, district engineer, C. B. White, district engineer, and McHenry Mosier, chief, College Park Division, Mining Branch.The geophysical section of the exploration was performed by G. B. Botsford, engineer of the Bureau of Mines. Assistance was given by the Division of Geophysical Exploration of the Bureau of Mines, Dr. F. W. Leo, chief."